Problems and Prospects for the Development of Small Business (Entrepreneurship) and Employment in the Republic of Uzbekistan - Sodikova Aziza Maksudovna (Zien Journals, 2023)
The progressive development of small business is the most important factor in successfully resolving issues related to ensuring employment of the population and the effective use of the region’s labor resources. As the experience of developed countries shows, small and medium-sized businesses play a very important role in the economy, their development affects economic growth, the creation of additional jobs, the acceleration of scientific and technological progress, and the saturation of the market with goods of the required quality.
Keywords: Employment; small and medium-sized businesses; developed countries